Pentingnya Aktualisasi Keterampilan Interpersonal Eksekutif Demi Menciptakan Organisasi yang Efektif - Lelo Yosep Laurentius (Humaniora, 2013)
Research on close groups reveals that the construction of a shared reality in the minds of members as well as a shared view and appreciation of their work, the essence of effectiveness.  From the cases analyzed descriptive ensure that the most effective way is, perhaps, to give an example. Personal transparency of the leader disclosing important information about ideas and feelings which are relevant to the group work in a harmonious manner encourages the participation of others.